IMPLEMENTASI KURIKULUM TARBIYYATUL MUALLIMINAL ISLAMIYAH (TMI) DI PONDOK MODERN DARUL HIJRAH MARTAPURA DAN PONDOK MODERN AN-NAJAH PUTERA TAMBANG ULANG - Muhammad Hayatur Rahman (Tarbawi, 2026)
Tarbiyyatul mualliminal Islamiyah (TMI) curriculum is a curriculum that is developed by Gontor Modern Boarding School. Many Modern Boarding Schools adopt this curriculum as their boarding school`s curriculum. However, some Modern Boarding School that adopted this curriculum make a modification to the curriculum, without exception for An-Najah Modern Boarding School dan Darul Hijrah Modern Boarding School. This research purpose is to analysis idea, document, implementation, and study result of TMI curriculum. This research is a qualitative field study. Research data is collected by three approaches, namely interview, document view, and observation. Research data will be processed by interactive analysis data technic from Miles and Huberman which includes three steps from data reduction, data presentation, dan making conclusion. This research is applied in An-Najah Modern Boarding School in Tambang Ulang and Darul Hijrah Modern Boarding Scholl in Martapura which adopt TMI curriculum. This research aims to analyze the idea, document, implementation, and study results of the TMI curriculum. The research result shows that education purpose of modern boarding school is straight with national education purpose. Documentation of TMI curriculum includes education calender, syllabus and lesson plan of general and boarding school subjects which is its structure has been appropriate to national standard. Implementation curriculum in Modern Boarding School curricuulum consist of intracurricular, co-curricular, and extracurricular. Output of TMI curriculum is study completeness of students that is rated from their attendance, dicipline, and last examination score, and outcomes of TMI curriculum is alumnus those have many profession varieties.